Practical application of the CA-62 tumor marker in the initial diagnosis of oncological disease of epithelial origin: assistance to the doctor in interpreting the results - Janneta R. Tcherkassova; Sergei A. Tsurkan; Anna I. Prostyakova; Nikolai V. Suganov; Alexander M. Boroda; Albina I. Khamitova; Alexander P. Roytman (Consilium Medicum, 2023)
Aim. Demonstration the possibility of practical application of the highly sensitive tumor marker CA-62 in the initial diagnosis in asymptomatic patients with suspected cancer and/or the presence of pathological changes in instrumental studies, as well as describe the criteria for interpreting the results to help the doctor make a decision.